Cardiovascular risk calculation - James A. Ker (South African Family Practice, 2014)
Cardiovascular disease remains a major cause of global mortality and morbidity. Atherosclerosis is the main underlying cause in the majority of cardiovascular disease events. Traditional independent risk factors for cardiovascular disease include age, abnormal lipid levels, elevated blood pressure, smoking and elevated blood sugar levels (diabetes mellitus). These risk factors are incorporated into a risk score, such as the Framingham Risk Score (FRS), that is used to predict an individual’s absolute risk of a cardiovascular event, typically over the next 10 years, e.g. 15% risk over 10 years. These risk scores are useful in predicting risk in populations, but their ability to predict a cardiovascular event in an individual patient is not accurate and varies considerably across different populations. Currently, there are three methods of calculating cardiovascular risk. These are risk charts, e.g. FRS, a non-laboratory-based risk calculation, and lastly, screening for subclinical cardiac disease.